Modelo experimental de infusão rápida de cristaloide em ratos. - - Orgaes, Flávio Augusto Flório Stillitano de [UNESP] (2013)
It was described an animal model study of crystalloid rapid infusion in rats, discussing the clinical, laboratorial and histological results acquired with the administration of various amounts. Fifty six male Wistar rats were used with a medium weight of 318 (± 4) grams, divided randomly in seven groups of eight animals. The rats of groups 1 to 6 received lactated Ringer´s solution intravenously, in a rapid way (25 ml/min), in the amount of 0.5, 1, 1.5, 2, 2.5 and 3 fold its blood volume (BV), respectively, composing the study groups. The rats of group 0 were submitted to surgery the same way, but did not receive the crystalloid, composing the control group (SHAM). The laboratorial evaluation of blood and the clinical signs were made in two times (before and ten minutes after the fluid infusion). The gravimetric assessment of pulmonary edema (PE) was made with the left lung and the histological assessment with the right lung, both extracted after euthanasia. The data with two distinct times were analyzed through the difference between the moments, comparing to the control group with an analysis of variance, followed by Dunnett´s test. The evaluation of the lung wet weight/body weight ratio (LW/BW), the lung wet/dry weight ratio (W/D), histology and upshot were performed by an analysis of variance (ANOVA). The findings were significant at the 0.05 level. The clinical signs significantly changed in the 2, 2.5 and 3 fold BV groups. The hematocrit reduction was significant in the six study groups, corroborating the method effectiveness to promote hemodilution. The laboratorial blood exams significantly changed from 1 fold BV group. The PE was clearly identified by the gravimetric and histological assessment in the 2.5 and 3 fold BV. The respiratory arrest was observed in the 1.5, 2, 2.5 and 3 fold BV groups. The volume of 3 fold BV was lethal to all animals of the group. This animal model was easily performed ...